2011
DOI: 10.1107/s1600536811007999
|View full text |Cite
|
Sign up to set email alerts
|

Tetraaquabis[2-(2-oxo-2,3-dihydro-1,3-benzoxazol-3-yl)acetato]zinc

Abstract: The ZnII ion in the title compound, [Zn(C9H6NO4)2(H2O)4], is located on an inversion center and is octahedrally coordinated by two 2-(2-oxo-2,3-dihydro-1,3-benzoxazol-3-yl)acetate anions in axial sites and four water molecules in equatorial positions. In the crystal, O—H...O hydrogen bonds between the coordinated water molecules and carbonyl–carboxylate O atoms lead to pleated sheets parallel to (001)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…1. The geometric parameters of the arene and oxazole rings are similar to standard values and to those in other related structures (Ashurov et al, 2011(Ashurov et al, , 2015Wang et al, 2016). In the oxalate (OXL) part of the organic salt, two hydrogen atoms are transferred to the nitrogen of the oxazole fragments, as in other 2-aminobenzoxazole (2ABO) structures (Nandy et al, 2016;Razzoqova et al, 2022Razzoqova et al, , 2023.…”
Section: Structure Descriptionsupporting
confidence: 79%
“…1. The geometric parameters of the arene and oxazole rings are similar to standard values and to those in other related structures (Ashurov et al, 2011(Ashurov et al, , 2015Wang et al, 2016). In the oxalate (OXL) part of the organic salt, two hydrogen atoms are transferred to the nitrogen of the oxazole fragments, as in other 2-aminobenzoxazole (2ABO) structures (Nandy et al, 2016;Razzoqova et al, 2022Razzoqova et al, , 2023.…”
Section: Structure Descriptionsupporting
confidence: 79%
“…We present our results of both considerations in Table 2. (a) Three isomorphous complexes with the composition [ML 2 (H 2 O) 4 ] (M = Co II , Cu II and Zn II ) have been reported (Ashurov et al, 2011(Ashurov et al, , 2014. The benzoxazolone derivative acts as a carboxylato ligand coordinated through a single oxygen atom; thus no steric strain due to the chelation arises.…”
Section: Tablementioning
confidence: 99%
“…No structural study for this compound has been published to date, but it has been used as a ligand and successfully coordinated to divalent transition metal cations; crystal structures of the resulting mononuclear complexes have been reported (Ashurov et al, 2011(Ashurov et al, , 2014. In this contribution, we communicate the synthesis and characterization of the title compound.…”
Section: Introductionmentioning
confidence: 99%
“…About 20% of them feature zinc as a structural component (Banci et al, 2002;Andreini & Bertini, 2012). Zinc complexes exhibit a wide range of coordination numbers and coordination spheres, with tetrahedral (Ashurov et al, 2018;Petrus et al, 2020) and octahedral (Ashurov et al, 2011) environments being the most frequently observed.…”
Section: Chemical Contextmentioning
confidence: 99%